2021
DOI: 10.4018/ijaeis.20210101.oa2
|View full text |Cite
|
Sign up to set email alerts
|

IoT-Based Intelligent Irrigation System for Paddy Crop Using an Internet-Controlled Water Pump

Abstract: IoT is a communal association of things or equipment that can interact with each other with the help of an internet connection. IoT services play an imperative responsibility in the industry of agriculture, which can feed 10 billion people worldwide by 2050. Irrigation systems are a backbone of agriculture that help to reduce wastage of water and decide the effective usage of water according to the specific crop and thereby increase the crop yield. In this paper, an irrigation system is developed to supervise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The drip-irrigation system is advantageous in terms of reducing water consumption; however, water supply for rice crops in Korea comprises a supply system for continuous irrigation using water canals. Sharma and Kumar [29] proposed an irrigation system for paddy crops using IoT, which supplied water via a water pump based on soil moisture. Barkunan et al [30] proposed an automatic drip-irrigation system using a smart sensor for paddy cultivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The drip-irrigation system is advantageous in terms of reducing water consumption; however, water supply for rice crops in Korea comprises a supply system for continuous irrigation using water canals. Sharma and Kumar [29] proposed an irrigation system for paddy crops using IoT, which supplied water via a water pump based on soil moisture. Barkunan et al [30] proposed an automatic drip-irrigation system using a smart sensor for paddy cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…The automation of irrigation systems is a water-saving technology [28]. However, few studies [29,30] have reported on automated irrigation systems for rice cultivation. In the future, a business model that can automate paddy water management will be required to counteract the aging problem of farmers.…”
Section: Introductionmentioning
confidence: 99%
“…These methods have enabled efficient analysis and modeling of hydrometeorological data, which is crucial for sustainable water management. In addition, the controlled management of irrigation systems through the Internet of Things (IoT) and the use of big data and machine learning have proven to be essential for more efficient and environmentally sustainable water management, reducing costs and ensuring water quality for human consumption [36][37][38]. Estimation of daily potato crop evapotranspiration using three different machine learning algorithms and four scenarios of available meteorological data.…”
Section: Application Of Fertilizers Application Of Agrochemicalsmentioning
confidence: 99%
“…These systems can significantly contribute to the sustainability of water resources by ensuring that crops receive the precise amount of water needed, thus reducing waste and increasing crop yield. The significance of IoT-based irrigation systems is particularly pronounced in the context of water scarcity, a pressing issue that threatens food security, livelihoods, and overall agricultural productivity across the globe (Dickson & Amannah, 2023;Sharma & Kumar, 2021). This challenge is not confined to any single region but affects diverse agricultural landscapes, including both the arid zones of Africa and the water-stressed fields of the United States (Abioye et al, 2020).…”
Section: Introductionmentioning
confidence: 99%